Sistem Informasi Cuti Pegawai Berbasis Web Pada Universitas Jambi - Rachman, Abdul; Effiyaldi, Effiyaldi (Jurnal Manajemen Sistem Informasi, 2023)
Leave is one of the employee rights that must be given by a company. Issues regarding the licensing and leave of civil servants have been regulated in Law Number 11 of 2017 about management of civil servants. The process of applying leave at Jambi University is currently still done manually, checking the remaining leave, filing the form, approval and leave reports still rely on paper leave archives. The manual leave management process has several weaknesses. Employees cannot find out the remaining personal leave entitlements and another weakness is that the leave application process is less effective and efficient. The purpose of this research is to improve the deficiencies that exist in the current system and to simplify and speed up the employee leave management. In designing this prototype, the authors use a modeling tool in the form of Unified Modeling Language (UML) with Use Case Diagrams, Activity Diagrams and Class Diagrams.